2006
DOI: 10.1074/jbc.m600939200
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Inhibits Chondral Mineralization through Apoptotic Cell Death Mediated by Retrograde Operation of the Cystine/Glutamate Antiporter

Abstract: Although we have previously demonstrated the functional significance of excitatory amino acid transporters as well as glutamate (Glu) receptors (GluRs) expressed by chondrocytes, little attention has been paid to the possible expression of the cystine/ Glu antiporter responsible for the bi-directional transmembrane transport of Glu in chondrocytes to date. In organotypic cultured mouse embryonic metatarsals isolated before vascularization, the chondral mineralization was significantly decreased in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…This allowed us to investigate the effects of FK506 in an experimental system where chondrocytes retain their normal architecture of round and columnar prehypertrophic and hypertrophic zones. The absence of mesenchymal cells, other than chondrocytes, from any of the cell layers, except those in bone collar or perichondrium of cultured metatarsals, is already confirmed by in situ hybridization in our previous study (36).…”
Section: Discussionsupporting
confidence: 49%
“…This allowed us to investigate the effects of FK506 in an experimental system where chondrocytes retain their normal architecture of round and columnar prehypertrophic and hypertrophic zones. The absence of mesenchymal cells, other than chondrocytes, from any of the cell layers, except those in bone collar or perichondrium of cultured metatarsals, is already confirmed by in situ hybridization in our previous study (36).…”
Section: Discussionsupporting
confidence: 49%
“…To our knowledge, this is the first direct demonstration of a negative correlation between expression profiles of Runx2 and xCT subunit during osteoblastogenesis in ovariectomized mouse femurs in vivo and in pre-osteoblastic MC3T3-E1 cells in vitro. Although several previous studies including ours have already demonstrated the functional expression of the Xc − in several cells such as chondrocytes (20), dendritic cells (27), and meningeal cells (28), no direct evidence is available for a pivotal role of the Xc − in the cellular differentiation of osteoblas- Intracellular glutathione levels are regulated by the bidirectional Xc − system expressed at the cellular surface as a crucial determinant of the incorporation of extracellular cystine across plasma membranes to fuel the substrate cysteine in exchange for intracellular Glu in a variety of eukaryotic cells (12,15,16,29). Under the condition of high extracellular Glu levels, however, extracellular Glu is supposed to be taken up in exchange for intracellular cystine through the promoted retrograde operation of the Xc − , followed by decreased intracellular levels of GSH toward cell death mediated by GSH depletion (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of high extracellular Glu levels, however, extracellular Glu is supposed to be taken up in exchange for intracellular cystine through the promoted retrograde operation of the Xc − , followed by decreased intracellular levels of GSH toward cell death mediated by GSH depletion (15,16). Although marked apoptosis is induced by extracellular Glu at a high concentration, but not by agonists for any Glu-receptor subtypes, in association with GSH depletion in cultured rat costal chondrocytes (20), exposure to Glu at a high concentration leads to marked inhibition of cellular proliferation through a mechanism related to GSH depletion without inducing apoptotic cell death in osteoblastic MC3T3-E1 cells (17). It is thus conceivable that extracellular Glu at a high concentration could induce apoptosis through a mechanism associated with the depletion of intracellular GSH as a consequence of the promoted retrograde operation of the Xc − in chondrocytes, but not in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of ALP activity and Alcian blue staining were done as described previously (21). In brief, chondrocytes were solubilized with 0.1% Triton X-100 followed by determination of the ALP activity in lysates using p-nitrophenol phosphate as a substrate.…”
Section: Determination Of Alp Activity and Alcian Blue Staining-mentioning
confidence: 99%